Physiotherapy assessment and treatment of chronic subjective tinnitus using mechanical diagnosis and therapy: a case report. (14th March 2020) - Wu, Di; Ham, David; Rosedale, Richard
ABSTRACT: Objectives : Tinnitus is the perception of sound without any external auditory stimulus. Cervicogenic somatic tinnitus (CST) is a subset in which symptoms are modulated by maneuvers of the neck. The evidence for effective diagnosis and treatment of CST is limited. Mechanical Diagnosis and Therapy (MDT) is a biopsychosocial assessment and management system that uses the response to mechanical forces to classify clinical presentations accurately. The purpose of this case report is to describe the MDT assessment and management of a patient with chronic subjective tinnitus. Methods : A 67-year-old female with a 5-year history of left-sided subjective tinnitus, neck pain, and headache was referred for physiotherapy. Outcome measures included the Visual Analogue Scale (VAS), Tinnitus Handicap Inventory (THI), and Neck Disability Index (NDI). She was evaluated and treated according to MDT principles with management consisting of individualized directional preference exercises and postural correction. Results : Significant improvements in symptoms, cervical range of motion, function, and psychosocial status were observed over the long-term. At 6 months, THI scores dropped from 62/100 to 18/100 and NDI scores dropped from 18/50 to 3/50. Discussion : A comprehensive MDT assessment led to a classification of Derangement, with treatment focusing on tailored self-management. Contrary to other interventions described for CST, the patient was able to make significant and lasting changes to her symptoms without the need for any externally applied interventions. The emphasis on self-management dovetails well with the biopsychosocial model of care. This case provides preliminary evidence for the utility of screening for Derangement in conservative tinnitus assessments. Level of Evidence : 4